SIKAP ORANG TUA SISWA AUTIS PADA PEMBELAJARAN DALAM JARINGAN (DARING) DI SEKOLAH DASAR INKLUSIF KOTA YOGYAKARTA - Rahim, Abdul; Taryatman, Taryatman; Westri Andini, Dinar (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
Children with autism are part of children with special needs who experience complex developmental barriers related to emotions, behavior, social interactions, and communication. The learning process at home, help autistic children in learning many things that can be done by parents, among others, parents are expected to control, give instructions, provide guidance, and provide motivation. Parents' attitudes affect the way they treat their children, and their treatment of children, in turn, affects their children's attitudes toward them and their behavior. This study intends to reveal the attitudes of autistic parents in online learning which is reviewed in the cognitive, affective, and psychomotor domains at the Inclusive Elementary School in Yogyakarta City. The results showed that the attitude of parents of autistic children on the cognitive aspect showed negatif results with a percentage of 59.67%. While the affective aspect showed a negatif result of 51.5% and the conative aspect showed a positive result of 71%. According to research data, parental attitudes on cognitive and affective aspects showed negatif results, then on psychomotor aspects showed positive results. The data illustrates the need to increase parental knowledge about online learning strategies for autistic students.